Profile of a Faceted Macrostep Caused by Anomalous Surface Tension - Noriko Akutsu (Advances in Condensed Matter Physics)
The height profile of a macrostep on a vicinal surface near equilibrium is studied numerically using a restricted solid-on-solid model with a point-contact-type step-step attraction (p-RSOS model). We calculate the surface tension of vicinal surfaces around the (001) surface inclined towards the 111 direction using the density-matrix-renormalization group method. We also calculate the height profiles of vicinal surfaces using the Monte Carlo method and study the connection between the height profile of the macrostep near equilibrium and the discontinuous surface tension. We find that the height profile of a macrostep on a vicinal surface near equilibrium can be classified depending on the zone in the faceting diagram where the system exists. We also find finite size effects both for the height profile and for the inhibition of the macrostep motion in the relaxation process to the equilibrium state.